Divine evil - Roberts, Nora.; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1992)
A decade ago, sculptor Clare Kimball fled Emmitsboro, Maryland, to take the art world by storm. But no amount of success can eclipse the nightmares that haunt her - or the memories of her father's suicide. Emmitsboro sheriff Cameran Rafferty loved Clare from afar all through high school. Now that she's back, they form a bond that grows stronger each day. But Clare's past soon rises up with a vengeance, rocking the town with a sinister murder that is clearly linked to her return.
Originally published in hardcover: New York : Bantam Books, 1992.
Keywords: Satanism -- Fiction; Women sculptors -- Fiction; Fathers -- Death -- Fiction; Sheriffs -- Fiction; New York (N.Y.) -- Fiction; Maryland -- Fiction; Romantic suspense fiction